2014
DOI: 10.1089/jir.2014.0001
|View full text |Cite
|
Sign up to set email alerts
|

An RNA Editor, Adenosine Deaminase Acting on Double-Stranded RNA (ADAR1)

Abstract: Adenosine deaminase acting on RNA1 (ADAR1) catalyzes the C6 deamination of adenosine (A) to produce inosine (I) in regions of RNA with double-stranded (ds) character. This process is known as A-to-I RNA editing. Alternative promoters drive the expression of the Adar1 gene and alternative splicing gives rise to transcripts that encode 2 ADAR1 protein size isoforms. ADAR1 p150 is an interferon (IFN)-inducible dsRNA adenosine deaminase found in the cytoplasm and nucleus, whereas ADAR1 p110 is constitutively expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 107 publications
1
64
0
Order By: Relevance
“…Interestingly, we found that ADAR1 in hESCs was predominately localized to the nucleus (data not shown) as previously reported [49]. Consistent with its nuclear localization, ADAR1 interacted with endogenous DGCR8 (Figure 5B), but its interaction with DICER was barely detectable under our experimental conditions.…”
Section: Adar1 Acts As An Rna-binding Protein That Directly Inhibits supporting
confidence: 90%
“…Interestingly, we found that ADAR1 in hESCs was predominately localized to the nucleus (data not shown) as previously reported [49]. Consistent with its nuclear localization, ADAR1 interacted with endogenous DGCR8 (Figure 5B), but its interaction with DICER was barely detectable under our experimental conditions.…”
Section: Adar1 Acts As An Rna-binding Protein That Directly Inhibits supporting
confidence: 90%
“…We identified several DI-RNA sequences bearing clusters of A-to-G or U-to-C mutations and show through a computational approach that the sequences flanking the edited nucleotides, as well as the average editing frequency, were characteristic of ADAR1, but not ADAR2 (21). Of the three known ADARs, only the IFN-inducible ADAR1 isoform (also called p150) is cytoplasmic (58,59) and localizes to stress granules (56). These granules are induced during MV-C KO infection and form in close proximity to viral replication sites (14).…”
Section: Discussionmentioning
confidence: 99%
“…So far, many ADAR1 homologous sequences have been cloned and reported in vertebrates and invertebrates (George et al, 2014;Lynch, 2004;Mannion et al, 2014). ADAR1 is an IFN-induced gene involved in antivirus activity (Gelinas et al, 2011;Mangeat et al, 2012;Wu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%